The Effectiveness Of Nutrition Counseling Using The Main Menu Booklet Media For Pregnant Women On Vitamin C Intake And Compliance With Blood Supplement Tablets Consumption For Pregnant Women. - Swari, Sasmita Dewi Ratna; Sunarto, Sunarto; Pertiwi, Estuasih Dyah; Fitriyanti, Addina Rizky; Assidhiq, Mohamad Reza; Adyani, Kartika (JURNAL KEBIDANAN, 2025)
The number of anemia in pregnant women in the Bangetayu Health Center Area of ​​Semarang City is high. Data from 2018 showed that 34.3% of pregnant women who checked themselves at the Bangetayu Health Center experienced anemia.The aim of this study is to examine the proportion of vitamin C intake from the requirement, compliance of Iron-folic acid (IFA) supplementation consumption, and the effectiveness of nutrition counseling using the main menu booklet media for pregnant women. This study using randomized pre and post-test control group design, consisting of 2 groups, by which 24 treatment subjects and 24 control subjects. The data collection were gathered using informed consent, respondent’s identity, MMAS-8 questionnaire, 24-H food recall, and booklet as media intervention. Statistical analysis was performed in Shapiro-Wilk Test, One Way Anova, Independent T-Test, and Multiple linear regression.This study observed an increase the proportion of vitamin C intake from the requirement in treatment group from 90,3% to 154,4%, and an increase score in IFA supplement compliance from 3,7 to 4.0. Based on Multiple Linier Regression, nutrition counseling using the main menu booklet media was obeserved to increase in the proportion of vitamin C intake from the requirement is marginally significant(p=0,062) and increase score compliance IFA supplementation consumption is significant (p=0,034). Conclusion: Nutrition counseling using the main menu booklet media for pregnant women is increase the proportion of vitamin C intake from the requirement and compliance to IFA supplementation for pregnant women.